Emergency and routine presentation of neuroendocrine neoplasia in England: determinants of late presentation and survival outcomes - Marie Line El Asmar; Mohamed Mortagy; Benjamin E White; Dan Burns; John Ramage (Endocrine Oncology)
Objective: The time from onset of symptoms of neuroendocrine neoplasia (NEN) to diagnosis ranges between 5 and 7 years. Risk factors associated with this and the difference in overall survival (OS) between routine and emergency presentation (RP and EP) are not known. Design: A retrospective, population-based study. Methods: A retrospective, population-based study of gastroenteropancreatic and lung NEN registered on England’s national cancer between 2012 and 2021. Factors associated with worse OS, or emergency or late presentation (EP or LP), were evaluated using the Kaplan–Meier estimator, Cox and logistic regressions, and machine learning (ML) in two models. Results: A total of 21,345 NEN were included. 20.3% were EP. EP showed worse OS compared to RP. Factors associated with EP were male sex, advanced stage, worse deprivation and NEC. The ML model showed EP related to advanced stage, small intestinal NEN, NEC, advanced age, deprivation and male sex in decreasing order of importance. Factors associated with LP included EP, male sex and NEC. The ML model showed that NEC, small intestinal NEN, advanced age, EP and male sex are associated with LP in decreasing order of importance. Conclusion: EP is associated with poor survival. Addressing the associated factors may aid in timely diagnosis and improved survival.